Increased brain activation in motor cortex after acupuncture treatment for motor recovery in chronic stroke patients - Chau, Anson; Cheung, R.; Jiang, X.; Yeung, P.; Li, L. (Bentham, 2009)
Acupuncture has historically been recommended as adjunctive treatment to patients with stroke, but its effectiveness has yet to be proven. This case series aims to report the results of using functional magnetic resonance imaging (fMRI), together with motor function evaluations, to assess the effect of acupuncture on stable patients after stroke. Eleven chronic stroke patients underwent fMRI and motor function evaluations of their impaired upper limb before and after an 8-week period of acupuncture on two acupoints (Hegu LI-4 and Quchi LI-11), without undergoing simultaneous rehabilitation. Improvements in motor functions of the impaired upper limb were found after acupuncture treatment. Changes in cortical activities were closely related to the finding of improved motor functions. A larger and stronger activation was found in the sensorimotor area of the lesioned hemisphere after receiving the acupuncture intervention. Conjunction analysis demonstrated common regions that were activated during either motor task or acupuncture stimulation. Acupuncture may improve functions of the impaired upper limb in chronic stroke patients via modulating peri-infarct regions that are responsible for plasticity of the motor cortex.